Pengaruh Pemberian Biochar dan Kompos Terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) Pada Tanah Vertisol: The Effect of Biochar andCompost on the Growth of Pakcoy (Brassica rapa L.) On Vertisol Soils - Suryaningsih, Dwie Retna (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
Biochar is the remains of carbon that is not burned and has the form of powder or charcoal with small pores that can absorb and store nutrients and water. Therefore, the use of organic materials such as biochar and compost can help increase soil fertility and plant growth. The purpose of this study was to determine the extent to which the effect of biochar and compost on the growth of pakcoy plants on vertisol soils. This research method treated biochar and compost with the following treatment arrangements: A) B0 = control, B) B1 = 2% Biochar content, C) B2 = 4% biochar content, D) B3 = 6% biochar content, E) B4 = 2% compost content, F) B5 = 4% compost content, G) B6 = 6% compost content. The data obtained were processed statistically according to the 5% BNT variance analysis procedure to determine the effect of the treatment. The results of this study can be concluded that there is a treatment containing 6% biochar which is the best treatment for plant height parameters. While the treatment of 6% compost content is the best treatment on the number of leaves parameter.